Negative local resistance caused by viscous electron backflow in graphene - Bandurin, D A; Torre, I; Krishna Kumar, R; Ben Shalom, M; Tomadin, A; Principi, A; Auton, G H; Khestanova, E; Novoselov, K S; Grigorieva, I V; Ponomarenko, L A; Geim, A K; et al. (Science (American Association for the Advancement of Science), 2016)
Graphene hosts a unique electron system in which electron-phonon scattering is extremely weak but electron-electron collisions are sufficiently frequent to provide local equilibrium above the temperature of liquid nitrogen. Under these conditions, electrons can behave as a viscous liquid and exhibit hydrodynamic phenomena similar to classical liquids. Here we report strong evidence for this transport regime. We found that doped graphene exhibits an anomalous (negative) voltage drop near current-injection contacts, which is attributed to the formation of submicrometer-size whirlpools in the electron flow. The viscosity of graphene's electron liquid is found to be ~0.1 square meters per second, an order of magnitude higher than that of honey, in agreement with many-body theory. Our work demonstrates the possibility of studying electron hydrodynamics using high-quality graphene.